MANAJEMEN PEMBELAJARAN PONDOK PESANTREN TENTANG KEGIATAN MUZAKARAH DAN SOROGAN DALAM MENINGKATKAN KEMAMPUAN BACA KITAB KUNING STUDI KASUS PONDOK PESANTREN AT-THAHIRIYAH - HAYATIN NUFUS; ANIS ZOHRIAH; MACHDUM BACHTIAR (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2022)
This study aims to determine and describe the concept of learning management at Pondok Pesantren At-Thahiriyah regarding muzakarah and sorogan activities, knowing the role of ustadz and daily administrators in providing supervision to students in muzakarah and sorogan activities, knowing the evaluation of muzakarah and sorogan activities in improving reading ability of the yellow book. students at the At-Thahiriyah Islamic Boarding School, and to find out the various obstacles encountered by the At-Thahiriyah Islamic Boarding School in managing muzakarah and sorogan activities in improving the students' reading ability of the yellow book. The benefit is that good management of Islamic boarding school learning is very helpful in improving the ability to read the yellow book of students, especially at the At-Tahiriyah Islamic Boarding School. This research method uses descriptive qualitative. The selection of this method will make it easier to understand the data exposure that has been explained because it is arranged accurately and systematically. This data collection uses: observation, interviews, and documentation. The results of this study are: 1) the concept of learning management of muzakarah and sorogan activities in improving the ability to read the yellow book which includes lesson planning and learning implementation. 2) the role of the ustadz in muzakarah and sorogan activities in the form of controlling and supervising the learning process. 3) the evaluations given by Islamic boarding schools to students are divided into three, memorizing deposits, polar taftisyul, and musabaqah milad cottages. 4) supporting factors for the running of muzakarah and sorogan activities, among others, the performance of daily management and the education sector that coordinate with each other starting from planning, implementing and evaluating activities. Meanwhile, the inhibiting factors for muzakarah and sorogan activities emerged from the santri as the perpetrators of these two activities. ABSTRAKPenelitian ini bertujuan untuk mengetahui dan mendeskripsikan konsep manajemen pembelajaran Pondok Pesantren At-Thahiriyah tentang kegiatan muzakarah dan sorogan, mengetahui peranan ustadz dan pengurus harian dalam memberikan pengawasan kepada santri dalam kegiatan muzakarah dan sorogan, mengetahui evaluasi kegiatan muzakarah dan sorogan dalam meningkatkan kemampuan baca kitab kuning santri di Pondok Pesantren At-Thahiriyah, dan untuk mengetahui berbagai kendala yang ditemui Pondok Pesantren At-Thahiriyah dalam melakukan pengelolaan kegiatan muzakarah dan sorogan dalam meningkatkan kemampuan baca kitab kuning santri. Manfaatnya adalah bahwa manajemen pembelajaran pondok pesantren yang baik sangat membantu dalam meningkatkan kemampuan baca kitab kuning santri khususnya di Pondok Pesantren At-Thahiriyah. Metode penelitian ini menggunakan kualitatif deskriptif. Pemilihan metode ini akan mempermudah dalam memahami paparan data yang telah dijelaskan karena tersusun secara akurat dan sistematis. Pengumpulan data ini menggunakan: observasi, wawancara, dan dokumentasi. Hasil penelitian ini yaitu: 1) konsep manajemen pembelajaran kegiatan muzakarah dan sorogan dalam meningkatkan kemampuan baca kitab kuning yaitu meliputi perencanaan pembelajaran dan pelaksanaan pembelajaran. 2) peranan ustadz dalam kegiatan muzakarah dan sorogan berupa mengontrol dan mengawasi proses pembelajaran. 3) evaluasi yang diberikan pondok pesantren kepada santri terbagi menjadi tiga, setoran hafalan, taftisyul kutub, dan musabaqah milad pondok. 4) faktor pendukung berjalannya kegiatan muzakarah dan sorogan antara lain, adanya kinerja pengurus harian dan bidang pendidikan yang saling berkoordinasi satu sama lain mulai dari perencanaan, pelaksanaan dan pengevaluasian kegiatan. Sedangkan, faktor-faktor penghambat kegiatan muzakarah dan sorogan muncul dari santri sebagai pelaku dari kedua kegiatan tersebut.